2003
DOI: 10.1002/spip.171
|View full text |Cite
|
Sign up to set email alerts
|

A framework for capturing the relationship between usability and software architecture

Abstract: Usability is increasingly recognized as an essential factor that determines the success of software systems. Practice shows that for current software systems, most usability issues are detected during testing and deployment. Fixing usability issues during this late stage of the development proves to be very costly. Some usability‐improving modifications such as usability patterns may have architectural implications. We believe that the software architecture may restrict usability. The high costs associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 10 publications
1
55
0
4
Order By: Relevance
“…The selection of the chosen usability goal for prioritization was adopted from the analysis made by [11] that showed learnability, efficiency in use, reliability in use and subjective satisfaction were the most commonly cited. The method of prioritization and selecting prototype were adapted from [12,13] called Analytical Hierarchical Process (AHP), a multi-criteria analysis approach.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the chosen usability goal for prioritization was adopted from the analysis made by [11] that showed learnability, efficiency in use, reliability in use and subjective satisfaction were the most commonly cited. The method of prioritization and selecting prototype were adapted from [12,13] called Analytical Hierarchical Process (AHP), a multi-criteria analysis approach.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that user-centred design techniques are still underused among development teams [12] and most usability issues are only detected during testing and after deployment [13,14]. Of those practicing UCD, one investigation revealed that the majority of methods in practice were informal, low-cost user-centered design methods.…”
Section: Usability and Web Development Processesmentioning
confidence: 99%
“…Until recently [5,6] such relationships between usability and software architecture had not been described nor investigated. In [6] we defined a framework that expresses relationships between Software Architecture and Usability (SAU) based on our comprehensive survey [8].…”
Section: The Sau Frameworkmentioning
confidence: 99%
“…Many of the necessary usability changes to a system cannot be easily be accommodated by the software architecture. Certain usability improving solutions such as undo, user profiles and visual consistency have for particular application domains proven [5,6] to be extremely hard to retrofit during late stage development because they require architectural support. Restructuring the system during the later stages of development has proven to be an order of magnitude higher than the costs of an initial development [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation